2023
DOI: 10.1002/iid3.780
|View full text |Cite
|
Sign up to set email alerts
|

Risk of hepatitis B reactivation in HBsAg−/HBcAb+ patients after biologic or JAK inhibitor therapy for rheumatoid arthritis: A meta‐analysis

Abstract: Background The risk of hepatitis B virus (HBV) reactivation after biologic and targeted synthetic disease‐modifying antirheumatic drugs (b/tsDMARDs) therapy in patients with rheumatoid arthritis (RA) combined with HBsAg–/HBcAb+ is still inconsistent. Methods We conducted a systematic review of existing databases from 1977 to August 22, 2021. Studies of RA patients combined with HBsAg−/HBcAb +, treated with b/tsDMARDs and the reported number of HBV reactivation were incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 35 publications
(66 reference statements)
0
7
0
Order By: Relevance
“…An observational study of hepatitis B (HBV) reactivation in HBsAg À /HBcAb þ patients treated with various biologics found a pooled reactivation rate of 2.0%, with a 6.0% risk (95% CI 0.01-0.13) with abatacept, second only to rituximab (9% risk, 95% CI 0.04-0.15). Significantly lower rates of HBV reactivation were seen with JAKi, IL-6i, and TNFi [30].…”
Section: Abataceptmentioning
confidence: 89%
“…An observational study of hepatitis B (HBV) reactivation in HBsAg À /HBcAb þ patients treated with various biologics found a pooled reactivation rate of 2.0%, with a 6.0% risk (95% CI 0.01-0.13) with abatacept, second only to rituximab (9% risk, 95% CI 0.04-0.15). Significantly lower rates of HBV reactivation were seen with JAKi, IL-6i, and TNFi [30].…”
Section: Abataceptmentioning
confidence: 89%
“…9,10 A meta-analysis involving patients with RA receiving diseasemodifying antirheumatic drugs who were HBsAg-negative and HBcAb-positive was found to have a 1.0% pooled reactivation rate with JAK inhibitors. 11 A retrospective cohort study of patients receiving tofacitinib was able to show that 2 of the 6 HBsAg-positive patients developed HBVr. 12 HBVr with ruxolitinib use has also been documented.…”
Section: Discussionmentioning
confidence: 99%
“…The HBV reactivation rate was lower in HBsAg − /anti-HBc + individuals without antiviral prophylaxis. In a recent meta-analysis of HBsAg − /anti-HBc + patients with rheumatoid arthritis receiving IL-6 inhibitor therapy, the pooled reactivation rate was found to be 0.0% (4 studies; 1 reactivation in 162 patients; I 2 , 0%; P, 0.43) [ 11 ]. However, our own meta-analysis, which included a greater number of studies and a larger sample size (11 studies; 4 reactivations in 322 patients), demonstrated that this population still has a notable risk of HBV reactivation.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have addressed the risk of HBV reactivation in patients with severe COVID-19 receiving TCZ therapy [ 9 , 10 ]. The risk seems low in patients who are HBV-surface-antigen–negative/HBV-core-antibody–positive (HBsAg − /anti-HBc + ), and a short course of antiviral prophylaxis may be a safe option [ 11 ]. A study investigating the outcomes of 44 HBsAg − /anti-HBc + COVID-19 patients treated with tocilizumab [ 9 ] found that 61% of these patients received prophylactic entecavir.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation